Psychometric validation of the Persian version of the ethical awareness scale for nurses working in Iranian intensive care units - Shohreh Kolagari; Reza Moradi; Aimee Milliken; Homeira Khoddam (Wiley, 2024)
Abstract Aim The purpose of this study was to translate and validate the ethical awareness scale for nurses working in Iranian intensive care units. Design A cross‐sectional psychometric study. Methods The study was conducted in Oct 2020 to Sep 2021, involving the participation of 200 ICU nurses. The process included translation of the original version of the ethical awareness scale into Persian, following the World Health Organization guideline, for use in Iran. The translated version was then evaluated for reliability, face validity, content validity ratio, content validity index, convergent validity and construct validity. Results The initial reliability of the scale was established. In qualitative face validity, a few items changed slightly and all items were retained in the quantitative face validity assessment. Based on Lawshe's values, three items were removed from the scale during CVR assessment. All items exhibited acceptable CVI scores. Convergent validity was established with an average variance extracted greater than 0.5. The fit indices, such as CFI = 0.94, GFI = 0.94, RMSEA = 0.01, AGFI = 0.97 and CMIN/DF = 2.99, supported the structural model of the scale. The fit indices for the structural model of the scale were all within acceptable ranges, suggesting that the model fit the data well. Its reliability was confirmed through the test-retest method, with Cronbach's alpha = 0.84 and McDonald's omega coefficient >0.8. Conclusion The findings of this study indicate the Persian version of the ethical awareness scale for Iran (EAS‐IR) is comparable in content to the original version, demonstrating its validity and reliability for assessing ethical awareness among Iranian nurses in ICUs. The scale can be a valuable resource for measuring ethical awareness in the Iranian healthcare context and may contribute to improving ethical practices and decision‐making in ICU settings. Patient or Public Contribution In this project, no patient or public contribution was necessary, because it was not applied to our work.